Evolving microstructure, magnetic properties and phase transition in a mechanically alloyed Ni0.5Zn0.5Fe2O4 single sample - Ismayadi Ismail; Mansor Hashim; Samikannu Kanagesan; Idza Riati Ibrahim; Rodziah Nazlan; Wan Norailian; Wan Ab Rahman; Nor Hapishah Abdullah Dr. Fadzidah Binti Mohd Idris; Ghazaleh Bahmanrokh; Mohd Shamsul Ezzad Shafie; Masni Manap (Elsevier, 2024)
Volume :351